KEABSAHAN PENGHADAP YANG MENGHADAP SECARA DARING DALAM CYBER-NOTARY - Limantara, Nagawati; Barkatullah, Abdul Halim; Zulaeha, Mulyani (LPPM STIH Awang Long, 2023)
Progress in the digital era has made technological advances increasingly sophisticated and rapid so that the use of various digital media is very necessary for society. The shift in activities that were previously carried out conventionally is slowly shifting to online or better known as